Biogeographic Drivers of Evolutionary Radiations - Tao, Ran; Sack, Lawren; Rosindell, James (Frontiers in Ecology and Evolution, 2021)
Some lineages radiate spectacularly when colonizing a region, but others do not. Large radiations are often attributed to species’ adaptation into niches, or to other drivers, such as biogeography including dispersal ability and spatial structure of the landscape. Here we aim to disentangle the factors determining radiation size, by modeling simplified scenarios without the complexity of explicit niches. We build a spatially structured neutral model free from niches and incorporating a form of protracted speciation that accounts for gene flow between populations. We find that a wide range of radiation sizes are possible in this model depending on the combination of geographic isolation and species’ dispersal ability. At extremely low rates of dispersal between patches, each patch maintains its own endemic species. Intermediate dispersal rates foster larger radiations as they allow occasional movement between patches whilst sufficiently restricting gene flow to support further speciation in allopatry. As dispersal rates increase further, a critical point is reached at which demographically identical lineages may vary greatly in radiation size due to rare and stochastic dispersal events. At the critical point in dispersal frequency, some lineages remain a single species for a comparatively long time, whilst others with identical characteristics produce the largest radiations of all via a new mechanism for rapid radiation that we term a ‘radiation cascade’. Given a single species covering many patches connected with gene flow, a radiation cascade is triggered when stochastic dispersal is unusually low for a period, leading to an initial speciation event. This speciation means there are fewer individuals per species and thus further reduced gene flow between conspecifics. Reduced gene flow in turn makes it easier for further speciation to occur. During a radiation cascade, dispersal of individuals between patches continues at the same rate as before, but due to the increasing diversity it primarily introduces novel species that will later speciate, rather than adding to gene flow of existing species. Once a radiation cascade begins, it continues rapidly until it is arrested by a new equilibrium between speciation and extinction. We speculate that such radiation cascades may occur more generally and are not only present in neutral models. This process may help to explain rapid radiation, and the extreme radiation sizes of certain lineages with dispersing ancestors. Whilst niches no doubt play a role in community assembly, our findings lead us to question whether diversification and adaptation into niches is sometimes an effect of speciation and rapid radiation, rather than its cause.